Public‒private partnerships from sustainability perspective – a critical analysis of the Indian case. Issue 2 (2nd April 2016) - Patil, Nilesh A.; Laishram, Boeing
Abstract : Public‒private partnerships have become one of the preferred routes for governments to develop infrastructure, in view of the budgetary constraints faced by them and the efficiency gains provided by the private sector. Since the private sector is driven by profit-generation motives to enter a PPP arrangement, there are criticisms against PPPs for focusing on economic goals and financial targets while giving less emphasis to attainment of social objectives. As a result, infrastructure development through PPP will fail to promote sustainable development goals. The paper discusses the findings from a detailed review of Indian PPP procurement focusing on the shortcomings of infrastructure development through PPP in promoting sustainable development. A qualitative content analysis method was used to answer the research question 'Why have the key deliverables of the PPP procurement process failed to promote sustainable development goals?' The policy-makers and advisors of PPP projects could incorporate the key findings from the analysis in formulating new strategies for developing more sustainable PPP projects.